2016
DOI: 10.1016/j.jbi.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Unstructured medical image query using big data – An epilepsy case study

Abstract: Big data technologies are critical to the medical field which requires new frameworks to leverage them. Such frameworks would benefit medical experts to test hypotheses by querying huge volumes of unstructured medical data to provide better patient care. The objective of this work is to implement and examine the feasibility of having such a framework to provide efficient querying of unstructured data in unlimited ways. The feasibility study was conducted specifically in the epilepsy field. The proposed framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…[30] For mesial temporal sclerosis, Chupin et al identified hippocampus and amygdala atrophy from raw imaging data to within approximately 10% of the “gold standard” based on structural volume. [31,32] For cerebral aneurysm, Castro et al improved on an initial screen of ICD codes with a simple dictionary and classifier NLP to achieve 86% PPV. [12] For venous thromboembolism, Heit et al combined ICD codes and NLP to achieve 100% PPV and 94% NPV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30] For mesial temporal sclerosis, Chupin et al identified hippocampus and amygdala atrophy from raw imaging data to within approximately 10% of the “gold standard” based on structural volume. [31,32] For cerebral aneurysm, Castro et al improved on an initial screen of ICD codes with a simple dictionary and classifier NLP to achieve 86% PPV. [12] For venous thromboembolism, Heit et al combined ICD codes and NLP to achieve 100% PPV and 94% NPV.…”
Section: Resultsmentioning
confidence: 99%
“…[29] For cortical dysplasia, Kassubek extracted information from raw imaging data, successfully identifying dysplasia locations in seven out of seven patients, using 30 controls as a reference. [30] For mesial temporal sclerosis, Chupin et al identified hippocampus and amygdalaatrophy from raw imaging data to within approximately 10% of the "gold standard" based on structural volume [31,32]. For cerebral aneurysm, Castro et al improved on an initial screen of ICD codes with a simple dictionary and classifier NLP to achieve 86% PPV [12].…”
mentioning
confidence: 99%
“…Academic as well as business intelligence literature counsels are available for assisting transformation of big data into a selection of data assembled for care of single disease entities ( http://www.sas.com/ and http://www.aacc.org/ ). Structuring of such information for particular disease states is crucial [ 27 ] and platforms for gene sets might improve understanding different biological data types to reach meaningful outputs [ 28 ]. Web mapping and power-grid including care for people on a medical device that depends on electricity may be included.…”
Section: An Attempt To Categorizementioning
confidence: 99%
“…This framework has been used in the implementation of various applications, such as disease prediction in patients, diagnosis of cancer, patient emergency alerts, generation of disease decision rules, medical data quality assessment, and personalized recommendation systems. [4][5][6][7][8][9][10] In precision medicine, a patient's unique characteristics are used to tailor treatment in a manner that might be more elaborate than the standard course. For example, cardiologists currently use an algorithm that for a given patient predicts the occurrence of a myocardial infarction within 5 or 10 years based on body weight, arterial pressure, smoking status, blood lipid analysis results, and personal and family cardiovascular history.…”
Section: B R I E F R E P O R Tmentioning
confidence: 99%